PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP KINERJA PARAMEDIS PADA RSUD PEMKAB. KUANTAN SINGINGI - Yonna Oktavia; Sri Indarti; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aim to know how influence Leadership variable And Discipline by simultan and parsial of paramedic performance at RSUD Pemkab. Kuantan Singingi. Population in this research is counted 160 people from all doctor and nurse at RSUD Pemkab. Kuantan Singingi. Used data by analysis is descriptive, despitefully also use quantitative analysis that is using double linier regresi constructively SPSS version program 17. From result of examination wich have been simultan regresi tsest (uji-F) indicate that Leadership And Discipline by simultan have been effect on signifikan to paramedic performance. Result of test parsial (Test t) indicating that leadership by parsial have an effect on signifikan to paramedic performance. And also discipline variabel by parsial have an effect on signifikan of paramedic performance at RSUD Pemkab. Kuantan Singingi.Keywords: Leadership, Discipline, and Performance